A single dose of S‐ketamine induces long‐term antidepressant effects and decreases oxidative stress in adulthood rats following maternal deprivation. Issue 11 (19th March 2015) - Réus, Gislaine Z.; Carlessi, Anelise S.; Titus, Stephanie E.; Abelaira, Helena M.; Ignácio, Zuleide M.; da Luz, Jaine R.; Matias, Beatriz I.; Bruchchen, Livia; Florentino, Drielly; Vieira, Andriele; Petronilho, Fabricia; Quevedo, João
ABSTRACT Ketamine, an antagonist of N‐methyl‐d‐aspartate receptors, has produced rapid antidepressant effects in patients with depression, as well as in animal models. However, the extent and duration of the antidepressant effect over longer periods of time has not been considered. This study evaluated the effects of single dose of ketamine on behavior and oxidative stress, which is related to depression, in the brains of adult rats subjected to maternal deprivation. Deprived and nondeprived Wistar rats were divided into four groups nondeprived + saline; nondeprived + S‐ketamine (15 mg/kg); deprived + saline; deprived + S‐ketamine (15 mg/kg). A single dose of ketamine or saline was administrated during the adult phase, and 14 days later depressive‐like behavior was assessed. In addition, lipid damage, protein damage, and antioxidant enzyme activities were evaluated in the rat brain. Maternal deprivation induces a depressive‐like behavior, as verified by an increase in immobility and anhedonic behavior. However, a single dose of ketamine was able to reverse these alterations, showing long‐term antidepressant effects. The brains of maternally deprived rats had an increase in protein oxidative damage and lipid peroxidation, but administration of a single dose of ketamine reversed this damage. The activities of antioxidant enzymes superoxide dismutase and catalase were reduced in the deprived rat brains. However, ketamine was also able to reverse these changes. In conclusion, these findings indicate that a single dose of ketamine is able to induce long‐term antidepressant effects and protect against neural damage caused by oxidative stress in adulthood rats following maternal deprivation. © 2015 Wiley Periodicals, Inc. Develop Neurobiol 75: 1268–1281, 2015